QUANTIFICATION OF TRANS-ZEATIN IN CORN WASTES AND LIQUID ORGANIC FERTILIZERS BY HPLC CHROMATOGRAPHY - Choez, I.; Santana, P.; Peralta, E. (Emirates Journal of Food and Agriculture, 2014)
The trans-zeatin and other phytohormones are used as growth regulators to be induced in plants. Their presence has been determined in corn grains and some plant species, but not in their waste or liquid organic fertilizers, so the objective of this investigation was to quantify the compound by high performance liquid chromatography (HPLC). Ethanol extracts of corn waste and bioinsumos were prepared. Were identified by thin layer chromatography on aluminum chromatoplates Merck 60 F254 10x10cm as stationary phase and methanolacetonitrile (80:20) as mobile phase. Their quantification was performed by HPLC on a C18 column, 250mm x4 mm (5 ?m), and methanol-water (40:60) acidified 5% acetic acid as mobile phase, 0.8 mL.min-1 flow rate and wavelength of 280 ?m. The extract of corn grains was taken as control. Statistical analysis to validate the results obtained was performed in the InfoStac software. The control sample was found to have the highest concentration of trans-zeatin (0.730 mg / g). These results have not been referenced in the literature and allow adding ecological and economic utility of this type of agricultural waste.